Pengetahuan Pasien Tuberculosis dalam Menjalankan Program Pengobatan Obat Anti Tuberculosis (OAT) - I Gusti Ketut Gede Ngurah (Jurnal Gema Keperawatan, 2014)
This study to determine the level of patient compliance tuberculosis treatment program run anti-tuberculosis drugs (OAT) in Wangaya Hospital. This type of research is a descriptive study that aimed to describe or explain events - important events that happened today. Way of sampling used is Non-Probability Sampling (Consecutive Sampling) that takes a sample by assigning subjects who met the study criteria included in the study until a certain time, so that the respondent meets the criteria for a sample of 38. Most respondents have a high level of compliance is as much as 28 respondents (74%) of the 38 respondents. Dominant in the age range of 36-45 years were 12 respondents (31%), graduated from junior high school by 9 respondents (23%), and has a medication oversight (PMO) families were 26 respondents (68%). Researchers suggest for nurses in the room is expected to maintain a high level of patient compliance, and trying to further improve health education on the importance of uninterrupted treatment and the impact it had on drug with drawal PMO especially for patient families.